Japan and Iceland: Adventure Isles Nonni’s stay in Japan 1937–1938 - Ingvarsdóttir, Kristín (Milli Mála, 2021)
Late in his career as an author, Jón Sveinsson, Nonni, realised his dream of visiting Japan and nowhere did he feel that he had met with a better reception than in Japan. This despite the fact that Jón was among the best known and most widely travelled Icelanders of his time, as his popular children’s books had been translated into around 30 languages. He arrived in the spring of 1937, to spend a year at the well-known Sophia University, run by his fellow Jesuits in Tokyo. The present article aims to cast light on Jón’s stay in Japan and whereand how the writer and his works were discussed in contemporary Japanese newspapers and magazines. As Jón Sveinsson’s stay in Japan attracted a great deal of attention, media reports were both frequent and extensive. This article is based on sources gathered by the author from mainly Japanese archives and databases. These sources add a new perspective to previous research conducted on Jón Sveinsson’s Japan visit. Emphasis is also placed on the significance of the social and religious changes gaining prominence in Japan in the first half of the last century, which undoubtedly influenced the reception of the author and his work. The role and position of Sophia University in Japanese society is also examined, together with the complicated status of Christianity and the Jesuits in Japan in the years preceding World War II, which were characterised by ascending imperialism, nationalism, state Shinto and armed aggression on the Asian continent.Keywords: Jón Sveinsson – Nonni, Japan, reception (media coverage), travel literature, religion Seint á rithöfundarferli Jóns Sveinssonar, Nonna, rættist draumur hans um að ferðast til Japans og hvergi fundust Jóni viðtökurnar betri en einmitt þar. Jón var þó þekktur víða um lönd og einn víðförlasti Íslendingur síns tíma, enda höfðu barnabækur hans verið þýddar á um 30 tungumál. Jón kom til Japans vorið 1937 og dvaldist í eitt ár við hinn þekkta Sophia-háskóla í Tókýó, sem rekinn var aftrúbræðrum hans í Jesúítareglunni. Markmiðið með ...